Re-assessing the relationship between external political parties and student political bodies in the light of academic freedom and institutional autonomy - Shozi-Nxumalo, T.; Onwuegbuchulam, S.P.C. (South African Journal of Higher Education, 2025)
The establishment of student leadership bodies at Higher Education Institutions (HEIs) is central towards facilitating a good relationship between students and management and for catering for the well-being of students at HEIs generally. On paper, Student Representative Councils (SRCs) as part of the HEI system in South Africa are supposed to function autonomously to be effective in carrying out and enhancing students’ relationship with University management. However, university autonomy has experienced a significant decline, impacting both academic freedom and public accountability. This decrease is attributed to various factors, including administrative restrictions, laws, and regulations. There has also been a notable incursion and interference by external political parties in student politics at different HEIs in South Africa. Notably, there is a lack of discussion about the influence of student political organisations and their connections with external political parties regarding the discourse on institutional autonomy. Against the backdrop of the above-stated problem, the study adopts a phenomenological qualitative approach, utilising both primary and secondary data to reassess the relationship between external political parties and student political bodies in light of the notion of academic freedom and institutional autonomy. Key findings revealed that the relationship between external political parties and student political organisations influences institutional autonomy and ultimately the policies. The inability of universities to have oversight of these relationships leads to a lack of public accountability from both the institutions and the government. Despite universities being seen as places where there is autonomy and where academic freedom can be fully exercised, the findings indicate, among other points, that the partisanship of student leaders affects the autonomy of higher education institutions. These findings continue to add to the discussion on student leadership and partisanship, which also has implications for the operations of public higher education institutions in South Africa